Comparative transcriptome analysis of different chemotypes elucidates withanolide biosynthesis pathway from medicinal plant Withania somnifera - Gupta, Parul (Sci Rep, 2015)
Withania somnifera is one of the most valuable medicinal plants synthesizing secondary metabolites known as withanolides. Despite pharmaceutical importance, limited information is available about the biosynthesis of withanolides. Chemo-profiling of leaf and root tissues of Withania suggest differences in the content and/or nature of withanolides in different chemotypes. To identify genes involved in chemotype and/or tissue-specific withanolide biosynthesis, we established transcriptomes of leaf and root tissues of distinct chemotypes. Genes encoding enzymes for intermediate steps of terpenoid backbone biosynthesis with their alternatively spliced forms and paralogous have been identified. Analysis suggests differential expression of large number genes among leaf and root tissues of different chemotypes. Study also identified differentially expressing transcripts encoding cytochrome P450s, glycosyltransferases, methyltransferases and transcription factors which might be involved in chemodiversity in Withania. Virus induced gene silencing of the sterol ∆7-reductase (WsDWF5) involved in the synthesis of 24-methylene cholesterol, withanolide backbone, suggests role of this enzyme in biosynthesis of withanolides. Information generated, in this study, provides a rich resource for functional analysis of withanolide-specific genes to elucidate chemotype- as well as tissue-specific withanolide biosynthesis. This genomic resource will also help in development of new tools for functional genomics and breeding in Withania.